Differences in Ear Rot Resistance and Fusarium verticillioides-Produced Fumonisin Contamination Between Polish Currently and Historically Used Maize Inbred Lines - Czembor, Elżbieta; Waśkiewicz, Agnieszka; Piechota, Urszula; Puchta, Marta; Czembor, Jerzy H.; Stȩpień, Łukasz (Frontiers in Microbiology, 2019)
Poland is the fifth largest European country, in terms of maize production. Ear rots caused by Fusarium spp. are significant diseases affecting yield and causing grain mycotoxin contamination. Inbred lines, which are commonly used in Polish breeding programs, belong, mostly, to two distinct genetic categories: flint and dent. However, historically used lines belonging to the heterotic Lancaster, IDT and SSS groups were also present in previous Polish breeding programs. In the current study, 98 inbred lines were evaluated across a 2-year-long experiment, after inoculation with F. verticillioides and under natural infection conditions. Lancaster, IDT, SSS and SSS/IDT groups were characterized as the most susceptible ones and flint as the more resistant. Based on the results obtained, the moderately resistant and most susceptible genotypes were defined to determine the content of fumonisins (FBs) in kernel and cob fractions using the HPLC method. Fumonisin's content was higher in the grain samples collected from inoculated plants than in cobs. The association of visible Fusarium symptoms with fumonisin concentration in grain samples was significant. Conversely, the cobs contained more FB1 under natural infection, which may be related to a pathogen's type of growth, infection time or presence of competitive species. Using ddRADseq genome sampling method it was possible to distinguish a basal relationship between moderately resistant and susceptible genotypes. Genetic distance between maize genotypes was high. Moderately resistant inbreed lines, which belong to IDT and IDT/SSS belong to one haplotype. Genotypes which belong to the flint, dent or Lancaster group, and were characterized as moderately resistant were classified separately as the same susceptible one. This research has demonstrated that currently grown Polish inbred lines, as well the ones used in the past are a valid source of resistance to Fusarium ear rot. A strong association was observed between visible Fusarium symptoms with fumonisin concentration in grain samples, suggesting that selection in maize for reduced visible molds should reduce the risk of mycotoxin contamination. NGS techniques provide new tools for overcoming the long selection process and increase the breeding efficiency.